KESANTUNAN TINDAK TUTUR DIREKTIF KEPALA SEKOLAH TERHADAP GURU DI SMA NEGERI 1 KASIMBAR - Dewi, Made Kartika (BAHASANTODEA, 2016)
Language is the tool of communication for the human in their daily activity. As a tools of communication, the existing of language wish can help the human to fluency all of their activities. All of the activities which done by the human will not from whom which conveys the information is mentioned Speaker and speaker group or can be mentioned speak opponent. The speech which have relation with a context most influenced by the situation of speech. Its in the good condition in the people or in the school. In the interact of the school, head master who a person most have done meetings with the teacher. It enables will show that kinds of form directive speech action when the head master interacts with the teacher. The objective of the research is to describe the using of directive speech action which include (1) form, (2) Function, (3), speech strategy of head master in SMA Negeri 1 Kasimbar. The method which used in this research descriptive qualitative. The data accumulation is done with two techniques those are recording and observation. The subject of this research is a head master. The dataÂ  Analisys technique in this research is interactive model. The analisys in this include four steps, there are (1), accumulation data, (2), reduction data, (3), serving data, (4), verification/ take a conclude. The result of this research show that directive speech action form of head master to the teacher in SMA Negeri 1 Kasimbar consist of (1), imperative form, request form, (3), prohibition form, (4), giving a suggestion form, (5) statement form and (6) questioning form. The function of directive speech action is found of the research result which consist of (1) imperative function, (2) requesting function, (3) prohibition function, (4) giving a suggestion function. The strategy which used in directive speech action consist of direct strategy and indirect strategy. At the direct strategy, consist of (1) direct strategy in a imperative, (2) direct strategy in a request, (3) direct strategy in a prohibition, and (4) drect strategy in giving a suggestion. While indirect strategy that is (1) indirect strategy in a statement and indirect strategy in a question.